The Effects of a Multi-Ingredient Performance Supplement Combined with Resistance Training on Exercise Volume, Muscular Strength, and Body Composition - Dean Directo; Michael W.H. Wong; Marcus L. Elam; Paul Falcone; Adam Osmond; Edward Jo (MDPI AG, 2019)
The effects of a multi-ingredient performance supplement (MIPS) incorporating a mixture of branched chain amino acids, beta-alanine, glutamine, creatine, and piperine on resistance training (RT)-induced adaptations remains unclear. Therefore, the purpose of this study was to investigate the effects of this investigational MIPS during six weeks of RT on performance and body composition. Thirty recreationally trained males and females were recruited for this pair-matched, double-blind, placebo-controlled investigation. Subjects were assigned to consume either an experimental MIPS (MIPS) (n = 15) or a placebo (PLA) (n = 15) concurrently with a six-week periodized RT program. Body composition, one-repetition maximum (1RM), and muscular power were assessed at pre- and post-training. Weekly relative volume load was compared between groups. The MIPS and PLA groups demonstrated a significant increase in total body mass (MIPS = +2.9 ± 1.3%; PLA = +2.5 ± 1.7%) and lean mass (MIPS = +5.0 ± 2.1%; PLA = +3.1 ± 1.9%) (p < 0.001) with no changes in fat mass. There were no group × time interactions for any of the body composition measures. Both groups demonstrated similar improvements in maximum strength for the back squat, bench press, and deadlift as well as lower body power from pre- to post-training (p < 0.001). Within the limitations of the current investigation, results failed to demonstrate the benefits of the experimental MIPS for muscular strength and body composition across six weeks of RT compared to PLA.